Attitudes toward fertility and childbearing among female University students - Derya Yüksel KOÇAK; Nuriye Büyükkayacı Duman; Rukiye HOBEK AKARSU (Universa Medicina, 2023)
BACKGROUNDIn recent years, there has been a significant decrease in childbearing rates in many parts of the world. Young people who delay their marriage plans for various reasons also indirectly delay their childbearing to advanced ages. Postponed childbearing may lead to increased health risks for both mother and child. This study aimed to determine attitude towards fertility and childbearing in female university students. METHODSThis cross-sectional study involved 259 female university students. The data were collected with Attitudes Toward Fertility and childbearing Scale (AFCS). Data were analyzed using t test and one-way ANOVA. RESULTSIn the study 92.7% of the students wanted to become a future mother. The importance of fertility for the future mean score of the students with low income level (21.56±8.14) was found to be lower than the students with medium (25.80±6.51) and high income level (25.29±4.37) (p<0.05). The importance of fertility for the future mean score of only-child students (22.57±7.09) was lower than that of the other students (25.82±6.45). The importance of fertility for the future mean score of the students who did not have a date was also found to be lower than the students who had a date (p<0.05). CONCLUSIONIn the study, students with a low income level, who are an only child and who do not have a date during the study care less about fertility for the future. Also, students with a single-parent family, with siblings, and no previous sexual intercourse identify childbearing more with female identity.